Writing knowledge, practices, efficacy, interests, attitudes, and beliefs of deaf education teachers: a randomized controlled trial - Wolbers, Kimberly; Dostal, Hannah; Graham, Steve; Branum-Martin, Lee; Allen, Thomas; Holcomb, Leala; Saulsburry, Rachel (Frontiers in Psychology, 2023)
Writing teachers play an extraordinarily important role in their students' writing development. Teachers' motivational beliefs, such as attitudes toward writing, perceptions of their efficacy to teach writing, or preparation to use evidence-based instructional practices, impact their writing instruction, which directly affects the advancement of students' writing skills. Deaf and hard of hearing (DHH) writers are a subpopulation of writers who may face additional discriminatory beliefs toward their writing development stemming from ableism, audism, or linguicism. Deaf education teachers may doubt their abilities to teach bilingual/multilingual DHH students or teach deafDHH students experiencing language deprivation. The current study investigates whether deaf education teachers' beliefs can be fostered through an intensive one-year professional development (PD) program designed